Evaluation of seizures of live wild animals in Mexico - Patricia Frías-Álvarez; Gustavo Ortiz-Millán (Nature Conservation)
In Mexico, the illegal use of wildlife includes any activity related to wildlife that does not comply with current regulations. Seizure is an administrative sanction imposed by the Federal Attorney for Environmental Protection (PROFEPA) as a result of non-compliance with established regulations. There is a lack of official and accessible data on the number and species used and traded illegally in the country. This study aims to identify the species and the number of live wild animals seized by PROFEPA from 2012 to 2023, based on data requested by the National Institute for Transparency, Access to Information, and Personal Data Protection (INAI). During this period, a total of 17,662 live individuals belonging to 579 identified species were seized by PROFEPA. The taxonomic groups seized included mammals, birds, reptiles, amphibians, fish, mollusks, crustaceans, insects, arachnids, and other invertebrates. Birds were the group with the highest number of species seized. The 32 states in the country have records of seizure. A total of 60.3% of the species native to Mexico are included in some category of national risk. Over a nine-year period, animal seizures decreased by 97%. A total of 25 different domestic destinations were reported for the animals after seizure. The number of wildlife seized does not accurately reflect the total number of animals used and trafficked illegally. The use and illegal trade of wildlife in Mexico represents a highly relevant issue that demands strengthening the actions taken so far to eradicate it.